Ribsy - Cleary, Beverly; Darling, Louis (New York, Morrow, 1987)
Separated from his owner, Henry Huggins, in a shopping center parking lot, an ordinary city dog begins a string of bewildering adventures.
Keywords: Dogs -- Fiction